SERVICE QUALITY OF BENGKULU CITY FIRE DEPARTMENT: Bobby Mandala Putra - Dialektika Publik (Dialektika Publik, 2017)
This study was aimed to investigate the service quality of Bengkulu City Fire Department in the field of fire fighting using five dimensions quality of public services, namely tangibles, reliability, responsiveness, assurance, and empathy as a research instrument. This study used a quantitative approach with a descriptive research which fouces on survey method. Primary data collection was done by giving questionnaires that have been tested for validity and reliability to the respondents, while secondary data collection was done by conducting a review of the literature and relevant research, fire incident reports and documentation activities related to research needs. Data analysis was performed using quantitative data analysis techniques namely descriptive statistics with SPSS for Windows version 20. The finding of the research showed that the quality of service Bengkulu City Fire Department in the field of fire fighting if it measured in a unit with five dimensions of quality of public services, namely tangibles, reliability, responsiveness, assurance, and empathy then the service quality of Bengkulu City Fire Department in the field of fire fighting had enough quality with a mean was 3, 39, median was 3.54, the modus was 3a, standard deviation was 0.614, the variance was 0.377, the minimum was 2, and the maximum was 5, however if it measured separately between the dimensions of the other dimensions, the quality of service of Bengkulu City Fire Department in the field of fire fighting was varied enough. It was proven by the average of respondents' answers on the dimensions of tangibles, and assurance stating that the quality of Bengkulu city fire fighting services had good quality, while the average of respondents on the other three dimensions, namely reliability, responsiveness, and emphaty had enough quality.